Public Legal Awareness of the Importance of Covid-19 Vaccination in Southeast Maluku Regency - Yosia Hetharie; Patrick Corputty (Faculty of Law, Universitas Pattimura, 2021)
The spread of Covid-19 has an impact on all areas of human life universally throughout the world to all corners of the region in Indonesia, including the Southeast Maluku Regency, Maluku Province. Therefore, the government through the covid-19 vaccination program is one way to break the chain of the spread of Covid-19. This study uses a normative juridical research which is descriptive analytical through primary legal materials and secondary legal materials with literature studies. The analysis used is qualitative analysis. The implementation of the Covid-19 vaccination in Southeast Maluku Regency continues to be carried out in order to meet the national achievement target of 70%. As of early November, it was shown that in Southeast Maluku the achievement rate of Covid-19 vaccination for both the first and second doses was still below the national target of 70 percent. By not meeting the national Covid-19 vaccination achievement target in Southeast Maluku Regency, it shows that the legal awareness of the community to vaccinate Covid-19 in Southeast Maluku is still very minimal. The Southeast Maluku Regency Government needs to approach the community that is more humanistic and socio-cultural in order to provide education and good understanding for the community about the Covid-19 vaccination so as not to cause doubts in the community to vaccinate Covid-19.